2014
DOI: 10.1007/s10396-014-0542-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-time tissue elastography (RTE) for noninvasive evaluation of fibrosis in liver diseases in children in comparison to liver biopsy

Abstract: RTE parameters enable a possible differentiation of high fibrosis; however, their correlation with fibrosis stage was moderate. RTE seems to be a promising method in liver fibrosis grading in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
7
0
4
Order By: Relevance
“…Published evidence obtained with SE in children is scarce and contradictory (Schenk et al 2014a(Schenk et al , 2014bSelmi et al 2014).…”
Section: Examination Technique and Normal Valuesmentioning
confidence: 99%
“…Published evidence obtained with SE in children is scarce and contradictory (Schenk et al 2014a(Schenk et al , 2014bSelmi et al 2014).…”
Section: Examination Technique and Normal Valuesmentioning
confidence: 99%
“…Regarding age, Schenk et al (5) found similar results in a study of 34 children (17 females and 17 boys, mean age 10.53 ±5.66 years), when comparing the usefulness of ultrasonic elastography to liver biopsy in pediatric liver disorders.…”
Section: Discussionmentioning
confidence: 60%
“…RTE measures, according to Schenk et al (5) , allow for the classification of high fibrosis, although their connection with the fibrosis stage is modest. RTE appears to be a viable approach for assessing liver fibrosis in youngsters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morikawa et al[67] analysed RTE in 101 adult patients with hepatitis c and found a good correlation of the RTE values with the histologic grading of fibroses. In contrast, data obtained from children in another study[68] showed only a moderate correlation, and it was concluded that RTE could not be recommended for a clear differentiation of fibrosis stages while the difference between stage IV fibrosis and normal liver tissue or stage I fibrosis was significant.…”
Section: Sonoelastrographymentioning
confidence: 84%